2014
DOI: 10.1117/1.jrs.8.083674
|View full text |Cite
|
Sign up to set email alerts
|

Integrating remotely sensed leaf area index and leaf nitrogen accumulation with RiceGrow model based on particle swarm optimization algorithm for rice grain yield assessment

Abstract: Abstract. A regional rice (Oryza sativa) grain yield prediction technique was proposed by integration of ground-based and spaceborne remote sensing (RS) data with the rice growth model (RiceGrow) through a new particle swarm optimization (PSO) algorithm. Based on an initialization/parameterization strategy (calibration), two agronomic indicators, leaf area index (LAI) and leaf nitrogen accumulation (LNA) remotely sensed by field spectra and satellite images, were combined to serve as an external assimilation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 27 publications
(34 reference statements)
3
24
0
Order By: Relevance
“…Ma [20] selected the Soil-water-atmosphere-plant environment (SWAP) model and the Moderate Resolution Imaging Spectroradiometer (MODIS) products to assimilate evapotranspiration and LAI and suggested that this could achieve a better yield estimation of winter wheat than the use of just one variable. Wang et al [18] confirmed that the use of LAI together with leaf N accumulation as assimilation variables resulted in a better estimation of winter wheat yield than using each variable alone for model parameter initialization.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Ma [20] selected the Soil-water-atmosphere-plant environment (SWAP) model and the Moderate Resolution Imaging Spectroradiometer (MODIS) products to assimilate evapotranspiration and LAI and suggested that this could achieve a better yield estimation of winter wheat than the use of just one variable. Wang et al [18] confirmed that the use of LAI together with leaf N accumulation as assimilation variables resulted in a better estimation of winter wheat yield than using each variable alone for model parameter initialization.…”
Section: Introductionmentioning
confidence: 55%
“…The primary reason for this is that LAI is a key variable for crop growth monitoring and yield prediction [58], and CNA is an important indicator of the N status of wheat and significantly affects photosynthetic production and grain yield and quality [59]. Various crop state variables are independent of each other, though they interact with each other [18,60]. Therefore, the SVLAI + CNA method obtained a greater robustness of the DSSAT-CERES model than the single variable methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rice simulation models are usually considered effective tools for the evaluation of rice production, previous models have been developed based on weather rice production relationships or field-scale observations (Horie et al, 1995;Bouman, 2001;Timsina and Humphreys, 2006;Yoshida and Horie, 2010). Accordingly, a combination with remotesensing has been explored to apply rice simulation models on a regional scale (Inoue et al, 1998;Oki et al, 2013;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Leaf area index (LAI), defined as half the total foliage area per unit ground horizontal surface area [1], is an essential biophysical property of vegetation for environmental assessment [2,3], crop growth monitoring [4,5] and yield prediction [6][7][8]. The accurate monitoring of LAI on multiple scales has become a key technique in those applications.…”
Section: Introductionmentioning
confidence: 99%